1328. Paenibacillosis: An Emerging Cause of Neonatal Sepsis and Postinfectious Hydrocephalus. (15th December 2022) - Ericson, Jessica E; Burgoine, Kathy; Hehnly, Christine; Kumbakumba, Elias; Ochora, Moses; Bajunirwe, Francis; Bazira, Joel; Fronterre, Claudio; Hagmann, Cornelia; Kulkarni, Abhaya; Senthil Kumar, M; Magombe, Joshua; et al.
Abstract: Background: The etiology of neonatal sepsis is often not identified. Molecular methods can identify pathogens that culture-based methods miss. Most cases of neonatal sepsis globally are treated empirically per WHO guidelines with intravenous ampicillin and gentamicin, which may not be the best regimen for all pathogens. Methods: We prospectively enrolled 800 neonates presenting with signs of sepsis to two Ugandan hospitals. Blood and cerebrospinal fluid were subjected to 16S rRNA sequencing, which identified Paenibacillus thiaminolyticus in 33/800 (4%) neonates. We confirmed the presence of P. thiaminolyticus by quantitative polymerase chain reaction (PCR). We describe neonatal and birth characteristics, presenting signs, and 12-month developmental outcomes for neonates with paenibacillosis. We performed antibiotic susceptibility testing and genomic analyses on three clinical isolates successfully grown in the laboratory. Results: Neonates presented at a median age of 3 (1, 7) days. Fever (86%), irritability (78%) and seizures (52%) were common presenting signs (Figure). Most neonates were born vaginally (73%) at a medical facility (79%). Twelve (36%) had an adverse outcome: 5 (15%) neonates died; 4 (14%) survivors developed postinfectious hydrocephalus and three (9%) additional survivors had neurodevelopmental impairment. All three isolates were resistant to vancomycin, two were resistant to penicillin and ampicillin and one was unlikely to be sensitive to ceftriaxone; all were susceptible to gentamicin and meropenem. The genomes of all three strains contained multiple beta-lactamase genes and a cluster of genes that encodes a type IV pilus. Clinical signs at presentation for neonates with good and poor outcomes followng paenibacillosis Conclusion: Molecular methods such as 16S rRNA sequencing and PCR can be used to improve the identification of pathogens causing neonatal sepsis. Paenibacillosis is an important emerging cause of neonatal sepsis in Uganda and is likely an underrecognized cause of postinfectious hydrocephalus in the region and possibly elsewhere. Antibiotics commonly used for neonatal sepsis may be inadequate for the treatment of paenibacillosis. Additional studies to understand the pathophysiology and optimal treatment of this novel infection are urgently needed to prevent neonatal mortality and morbidity including postinfectious hydrocephalus. Disclosures: Jessica E. Ericson, MD, MPH, Abbvie: Advisor/Consultant Abhaya Kulkarni, MD, MSc, PhD, Medtronic: Advisor/Consultant.